Ready player one [videorecording (DVD)] - Spielberg, Steven, 1946-; Spielberg, Steven, 1946-; Sheridan, Tye, 1996-; Cooke, Olivia, 1993-; Mendelsohn, Ben; Cline, Ernest (Warner Bros. Entertainment, 2018)
When the creator of a virtual reality world called the OASIS dies, he releases a video in which he challenges all OASIS users to find an Easter egg, which will give the finder his fortune.